Management provisions and communication in crisis: the level of preparation by ten belgian organisations - Hambursin, Chistine (2010)
Preparing organizations in order to be aware of and undergo a crisis is important due to the fact that the threshold level that triggers off a crisis has considerably decreased in the last few years but the cost that the crisis engenders is still growing. T he object of this research is to observe whar happens in reality and to understand the real importance that organisations give to provision for an eventual crisis and more precisely to the communication issues that are inevitably linked to crisis. This research is not exhaustive but is centred on ten organisations, that all have the potential to know a crisis at a given time in their history. As a result of studying relevant literature, a grid of indicators has been created so as to evaluate the level of crisis prepararían undertaken by these ten organisations. The application of this grid and the discussion around its actual preparation has helped us to improve ir by adding indicators thart allow more appropriace identificarion of the risks connected to such issues.